Optimization of conditions for preparation of activated carbon from coconut husk fiber using responses from measurements of surface area and adsorption - Al-Aoh, H.A.; Mihaina, I.A.M.; Alzuaibr, F.M.; Althaqafy, A.D.; Maah, M.J.; Yahya, R.; Abas, M.R.B.; Tyagi, I.; Agarwal, S.; Gupta, V.K. (Chemic Publishing Company, 2016)
Coconut husk fiber-based activated carbon was synthesized using ZnCl2. Analytical technique such as SEM was used for the characterization of the developed activated carbon obtained from the carbon husk. Effects of various influential parameters are optimized using the Taguchi experimental design. The optimization of SBET with the percentage removal of 4-nitrophenol, methylene blue and acid red-27 dye were applied as standard responses, the optimized parameters for SBET were activation temperature of 800 °C, concentration of ZnCl2 of 50 % w/v, nitrogen flow rate of 100 cm3/min, activation time of 2 h and carbonization temperature of 300 °C. 4-Nitrophenol optimized conditions were: carbonization at 400 °C, impregnation with 5 % w/v ZnCl2 solution and activation at 700 °C for 2 h with nitrogen flow rate of 200 cm3/min. Except for the impregnation ratio, nitrogen flow rate and activation time in the case of methylene blue, the ideal conditions of the percentage removals of methylene blue and acid red-27 are almost equal to that of the SBET. The surface characteristics of the samples produced under optimal conditions were examined. There are no pores available in the surface of the coconut fiber compared to the surface of the other two samples prepared under ideal conditions. Moreover, the activated carbons prepared under these optimized conditions contain small amounts of oxygen and have neutral surfaces.